TABUNGAN CINTA YANG PECAH: DAMPAK DAN RISIKO PERCERAIAN AKIBAT PINJAMAN ONLINE TANPA SEPENGETAHUAN PASANGAN - Wulan Asmi Nurapipah; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
A This study aims to analyze the issue of the impact and risk of divorce due to online loans without the knowledge of the couple. Studies on divorce may often be discussed but for the reason that specific online loans do not yet exist. Online loans are facilities used to borrow money that are sheltered by online-based financial service providers. Online loans are one of the factors behind divorce in Boregah Village RT02/RW09, Cilampunghilir Village, Padakembang District, Tasikmalaya Regency. The method used in the research is qualitative with a descriptive approach with data collection techniques based on observations and interviews. Participants came from former married couples who divorced due to borrowing online loans without the couple's knowledge, which includes resource person 1 under the pseudonym Mentrari and resource person 2 under the pseudonym Rain.The act of borrowing online loans without the knowledge of the spouse is a wrong act because it is considered a betrayal. Loss of trust in the spouse leads to disharmony in the household. Limited communication is also a factor that causes a partner to feel lonely and have to make quick decisions when in urgent circumstances. Keep in mind that the act of borrowing online loans is not a solution to family financial problems, but instead raises new problems. Openness and honesty between spouses are needed to create harmony so that there is no divorce.